2015
DOI: 10.1364/ol.40.001342
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon dioxide detection based on cavity ring-down spectroscopy and a quantum cascade laser

Abstract: Monitoring of radiocarbon (C14) in carbon dioxide is demonstrated using mid-infrared spectroscopy and a quantum cascade laser. The measurement is based on cavity ring-down spectroscopy, and a high sensitivity is achieved with a simple setup. The instrument was tested using a standardized sample containing elevated levels of radiocarbon. Radiocarbon dioxide could be detected from samples with an isotopic ratio C14/C as low as 50 parts-per-trillion, corresponding to an activity of 5  kBq/m(3) in pure CO(2), or 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(106 citation statements)
references
References 16 publications
3
103
0
Order By: Relevance
“…As was shown in our previous papers considering the main 12 C 16 O 2 isotopologue (denoted here as 626), a fully ab initio dipole moment surface is capable of providing such a level of accuracy [2,3]. The next step is to address other isotopologues, which are ubiquitous in natural samples and may interfere with spectral lines of the main isotopologue as well as other species [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As was shown in our previous papers considering the main 12 C 16 O 2 isotopologue (denoted here as 626), a fully ab initio dipole moment surface is capable of providing such a level of accuracy [2,3]. The next step is to address other isotopologues, which are ubiquitous in natural samples and may interfere with spectral lines of the main isotopologue as well as other species [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low cost instrument described herein is well suited for precise measurements of ultra-trace gas species including radiocarbon [20, 21] and atmospherically relevant free radicals. This instrument has been used to measure birefringence in supermirror coatings [14] and may be applied in addressing other challenges in fundamental physics including the search for symmetrization postulate violations in molecular physics [22] and measurements of absolute number densities for magnetically-trapped ultra-cold molecules using absorption-based techniques [23].…”
mentioning
confidence: 99%
“…Recent advances in cavity ring-down spectroscopy are aiming at optically more robust and compact instruments that enable mobile or on-site applications. Using a continuous-wave QCL setup with an overall footprint of approximately 90 × 60 cm, Genoud et al (113) demonstrated radio carbon trace gas detection with a detection limit of 14 for both high spatial and temporal resolution. For the detection of reaction processes and mechanisms, for example, the role of methanol in catalytic reactions such as CO 2 hydrogenation or CH 4 oxidation, information on particularly fast changes of local concentration conditions are of considerable interest for efficiently monitoring the overall conversion reaction.…”
Section: Emerging Techniquesmentioning
confidence: 99%